Christian Reflections - Lewis, C. S. (Clive Staples), 1898-1963; Hooper, Walter (Michigan : Eerdmans Publishing Company, 1967)
This collection contains fourteen of Lewis's theological papers on subjects such as Christianity and literature, Christianity and culture, ethics, futility, church music, modern theology and biblical criticism, the Psalms, and petitionary prayer. Common to all of these varied essays are Lewis's uniquely effective style and his tireless concern to relate basic Christianity to all of life
Preface, by Walter Hooper -- Christianity and literature -- Christianity and culture -- Religion: reality or substitute? -- On ethics -- De Futilitate -- The poison of subjectivism -- The funeral of a great myth -- On church music -- Historicism -- The Psalms -- The language of religion -- Petitionary prayer: a problem without an answer -- Modern theology and biblical criticism -- The seeing eye
Bibliographical references included in "Preface" (p. vii-xvi)
Keywords: Christianity -- 20th century